Novel endophytic fungi with fungicidal metabolites suppress sclerotium disease - Thanapat Suebrasri (2020)
© 2020 Elsevier B.V. This study is aimed to investigate the antifungal activity of endophytic fungi isolated from Jerusalem artichoke (Helianthus tuberosus) and Ginger (Zingiber officinale) and Stemona root (Stemona tuberosa) against causative agent of southern stem rot Sclerotium rolfsii. The dual assay results showed that out of 110 fungal endophytes, Diaporthe phaseolorum BUP3/1 and Macrophomina phaseolina BUP2/3, isolated from Jerusalem artichoke and Daldinia eschscholtzii 2NTYL11 and Trichoderma erinaceum ST-KKU2, isolated from Stemona root and ginger could effectively inhibited the mycelial growth of S. rolfsii at 76.00, 41.20, 66.67 and 63.63%, respectively. The β-1,3 glucanase and chitinase activities of all endophytic fungi was determined which reached the maximum after 2 and 7 days of incubation, respectively. In addition, Scanning Electron Microscope (SEM) observation showed that T. erinaceum ST-KKU2 has predatory mechanism aginst S. rolfsii via coiling and invasion. Interestingly, our endophytic fungi T. erinaceum ST-KKU2 and D. eschscholtzii 2NTYL11 were the first species in their genera to produce polyketides group as 6-n-pentyl-2H-pyran-2-one (6PAP) and 2,3-dihydro-5-hydroxy-2-methyl-4H-1-benzopyran-4-one (DHMB), respectively, to control S. rolfsii. Moreover, the antagonistic mechanisms of all endophytes were determined in vivo under greenhouse condition. The endophytic fungi, T. erinaceum ST-KKU2 and D. eschscholtzii 2NTYL11 also showed high level of reduction of southern stem rot disease by 58.14% under pot experiment. Such effects were also higher than the effects of other endophytic fungi isolated from Jerusalem artichoke when tested under greenhouse condition. Our experiments showed the fungal endophytes isolated have potential for further development as a biocontrol agent in the future.